Drilling engineering - Azar, Jamal J., 1937-; Samuel, G. Robello (Tulsa, Okla. : PennWell Corp., 2007)
Coauthored by a leading drilling engineering professor/researcher and a well-experienced drilling research advisor, Drilling Engineering explains the fundamentals and field practices in drilling operations. This textbook is an excellent resource for drilling engineers, drilling supervisors and managers, and petroleum engineering students.
Drilling rig requirements, selection, and evaluation -- Drilling fluids, including functions, types, selection criteria, evaluation, rheology -- Drilling fluid hydraulics and design requirements -- Drillstring mechanics -- Drill bit mechanics, including types, operational requirements, optimization -- Well control mechanics -- Pore and fracture pressures prediction and application -- Directional, horizontal, and multilateral well drilling -- Cementing and casing design -- Drilling problems and solutions -- Overview of underbalanced, slim hole, and coiled tubing drilling
Includes bibliographical references (pages [454]-471) and index.
Keywords: Oil well drilling; Gas well drilling